Abundance of spring‐ and winter‐active arthropods declines with warming. Issue 4 (23rd April 2021) - Fitzgerald, Jacquelyn L.; Stuble, Katharine L.; Nichols, Lauren M.; Diamond, Sarah E.; Wentworth, Thomas R.; Pelini, Shannon L.; Gotelli, Nicholas J.; Sanders, Nathan J.; Dunn, Robert R.; Penick, Clint A.
Abstract: Because ectotherm activity and metabolism are sensitive to temperature, terrestrial arthropods may be especially responsive to ongoing climatic warming. Here, we quantified responses of arthropod abundance to two years of warming in an outdoor temperature manipulation experiment at Duke Forest, North Carolina, USA. Nine open‐top chambers were individually heated year‐round from 1.5° to 5.5°C above ambient temperature. From two years of monthly pitfall trapping, we collected and identified 4, 468 arthropods representing 24 orders. We initially predicted that arthropods would experience the greatest negative effects of experimental warming during the summer months, when temperatures reach their yearly maximum and arthropods may be close to their maximum thermal tolerance limits. Instead, we found that the strongest negative effects on arthropod abundance occurred during the winter and spring, when ambient temperatures are relatively cooler, whereas the effects of experimental warming on abundance were not significant during the summer or fall. During the spring of 2012, the warmest spring on record for the southeastern USA, total arthropod abundance declined 20% per °C of experimental warming. Abundance declines were driven largely by flies (Diptera), which were the most abundant insect order, representing approximately a third of all arthropods collected. The most abundant arthropod family, Mycetophilidae (fungus gnats), declined 64% per °C of warming during the spring of 2012. Although previous research on climatic warming has focused on the impact of maximum yearly temperatures on organismal performance, our results are more consistent with the cool‐season sensitivity hypothesis, which posits that arthropods adapted for cooler conditions are likely to face the strongest negative effects of warming during the cooler seasons.